2011
DOI: 10.1017/s0954579410000696
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing infant attachment security: An examination of treatment efficacy and differential susceptibility

Abstract: This randomized controlled trial examined (a) the efficacy of a brief intervention designed to increase the rate of secure infant attachment, (b) the differential susceptibility hypothesis, and (c) whether maternal attachment styles moderated the expected Treatment x Irritability interaction in predicting infant attachment outcomes. Although there was no main effect of treatment, a significant Treatment x Irritability interaction revealed intervention effects for the highly irritable infants only, thus support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
167
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(184 citation statements)
references
References 46 publications
7
167
2
Order By: Relevance
“…Specifically, the intervention was most effective for mothers with highly reactive infants; on the other hand, for mothers with low reactive infants, there was no association between gains in maternal sensitivity and attachment security. Similar specification of intervention effects has been observed using infant irritability and child negative emotionality as ES moderators [38][39][40]. The same investigators also provided the first data on a genetically informed ES intervention.…”
Section: Experimental Evidence Of Esmentioning
confidence: 66%
“…Specifically, the intervention was most effective for mothers with highly reactive infants; on the other hand, for mothers with low reactive infants, there was no association between gains in maternal sensitivity and attachment security. Similar specification of intervention effects has been observed using infant irritability and child negative emotionality as ES moderators [38][39][40]. The same investigators also provided the first data on a genetically informed ES intervention.…”
Section: Experimental Evidence Of Esmentioning
confidence: 66%
“…For example, the Strengthening Families Program (SFP) has received mixed support for improving family environment (Molgaard and Spoth, 2001;Riesch et al, 2012); whereas Circle of Security (COS), an intervention designed to promote parent-child attachment, has demonstrated improvements only in a few small studies to date (Hoffman et al, 2006;Cassidy, Ziv, et al, 2010;Cassidy, Woodhouse, et al, 2011). Some other approaches have been evaluated only in open trials, including the Attachment, Self-Regulation, and Competency (ARC) model (Arvidson et al, 2011;Hodgdon, Kinniburgh, et al, 2013) and Strengthening Family Coping Resources (SFCR) (Kiser, Donohue, et al, 2010;Kiser, Backer, et al, 2015).…”
Section: State Of the Evidence For Improving Outcomes For Children Exmentioning
confidence: 99%
“…In total, 30 studies were identified, 175,178,[180][181][182][183][184]188,189,191,[194][195][196]198,[200][201][202][203][205][206][207][208]211,212,218 29 of which were delivering an intervention in a hypothesised 'at-risk' group to improve attachment security 129,[175][176][177][178][180][181][182][183][184][185][186]189,191,[194][195][196]198,[200][201][202][203]205,206,208,211,…”
Section: Main Systematic Reviewmentioning
confidence: 99%
“…188 The studies were published between 1985 and 2012 and were undertaken in a variety of countries: five in the UK, 176,188,189,207,208 14 in the USA, 177,[180][181][182][184][185][186]191,194,196,200,201,205,211 three in the Netherlands, 178,198,203 three in Canada, 175,195,218 one in Germany, 202 one in Australia, 130 one in Italy, 206 one in Finland 212 and one in Lithuania. 183 l Eight studies were identified in the main systematic review that evaluated the intervention using a measure that assessed a disorganised pattern.…”
Section: Main Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation